Pengaruh Auditor Switching, Audit Tenure, dan Ukuran KAP Terhadap Audit Delay (Studi Kasus Pada Perusahaan Property dan Real Estate Yang Listing di BEI tahun 2020-2023) - Ananta Adi Firmansyah; Hermawan Triono; Enny Susilowati Mardjono; Dian Festiana Hadi Saputro (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study was conducted to obtain empirical evidence on the impact of auditor switching, audit tenure, and the size of the Public Accounting Firm (KAP) on audit delays in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2023. This study uses a quantitative descriptive approach with secondary data from the IDX as its source. Data analysis was carried out with the help of SPSS version 25 software, including descriptive statistical tests, classical assumption tests, and hypothesis tests. The results of the study indicate that auditor switching does not have a significant effect on audit delays with a significance value of 0.352> 0.000. However, the audit engagement period and KAP size separately have a significant effect on audit delays with a significance value of 0.000 <0.05 for both. Together, the three independent variables are proven to have a significant effect on audit delays with a significance value of 0.000 <0.05.